Lateral hydrological connectivity differentially affects the community characteristics of multiple groups of aquatic invertebrates in tropical wetland pans in South Africa - Dube, Trevor; Pinceel, Tom; De Necker, Lizaan; Wepener, Victor; Lemmens, Pieter; Brendonck, Luc (Wiley, 2020)
River–floodplain connectivity (i.e. lateral hydrological connectivity, LHC) can directly affect the community characteristics by promoting dispersal of organisms but can also have profound indirect effects by altering local habitat characteristics. A major challenge is to disentangle the relative importance of direct and indirect effects of LHC on organisms. Combining taxonomic data with trait information allows a more mechanistic understanding of how LHC affect biotic communities in floodplains.